Recent advances in electrochemical deoxygenative functionalization of alcohols and their derivatives - Yong Yuan; Lili Liu; Feng Zhang; Ya-Nan Zhang; Congde Huo (Tetrahedron Chem)
This mini-review discusses the recent breakthroughs for electrochemical deoxygenative functionalization of alcohols and their derivatives. A diverse range of deoxygenative transformations is described, including the deoxygenative arylation, heteroarylation, alkylation, allylation, hydrogenation, cyanation, amination, borylation, and carboxylation. We hope that this mini-review can promote the rapid development in the field of electrochemical deoxygenative functionalization of alcohols and their derivatives.